2021
DOI: 10.3390/ijms222313153
|View full text |Cite
|
Sign up to set email alerts
|

Differential Actions of Muscarinic Receptor Subtypes in Gastric, Pancreatic, and Colon Cancer

Abstract: Cancers arising from gastrointestinal epithelial cells are common, aggressive, and difficult to treat. Progress in this area resulted from recognizing that the biological behavior of these cancers is highly dependent on bioactive molecules released by neurocrine, paracrine, and autocrine mechanisms within the tumor microenvironment. For many decades after its discovery as a neurotransmitter, acetylcholine was thought to be synthesized and released uniquely from neurons and considered the sole physiological lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 115 publications
(157 reference statements)
0
16
0
Order By: Relevance
“…As these serve as a background measures for the visual detection of areas with elevated uptake, the reduction of bowel uptake may be relevant in terms of target/background ratio. In contrast, the salivary glands and the liver demonstrated a significant decrease in uptake with the use of butylscopolamine, probably due to its anticholinergic effect on the muscarinic tissues of the glandular ducts and the biliary system [ 28 ]. Thus, the biological effect of the premedication could also be verified and quantified by PET in non-GIT organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these serve as a background measures for the visual detection of areas with elevated uptake, the reduction of bowel uptake may be relevant in terms of target/background ratio. In contrast, the salivary glands and the liver demonstrated a significant decrease in uptake with the use of butylscopolamine, probably due to its anticholinergic effect on the muscarinic tissues of the glandular ducts and the biliary system [ 28 ]. Thus, the biological effect of the premedication could also be verified and quantified by PET in non-GIT organs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the biological effect of the premedication could also be verified and quantified by PET in non-GIT organs. Other organs with muscarinic acetylcholine receptors like inner ocular muscles, smooth muscles of the urogenital system or perspiratory glands can hardly be visualized with PET because of their small size or the retention of tracer-containing urine [ 28 ]. Because of the likewise reduction of uptake in the liver by butylscopolamine, a bowel-to-liver ratio, as it has been performed in former studies for comparison, may be ineligible [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address this concern, more must be learned about the molecular mechanisms that modulate progression from primary colon cancer to locoregional and distant metastases. An emerging area, and the focus of our current research, is the role muscarinic receptors (MRs) and alterations in post-MR signaling play in cancer progression ( Ali et al, 2021 ; Schledwitz et al, 2021a ; Tolaymat et al, 2021 ). The five MR subtypes, M 1 R–M 5 R, respectively, encoded by CHRM1 - CHRM5 , are G protein-coupled receptors comprised of seven transmembrane helix domains with an extracellular acetylcholine (ACh)-binding region, and extracellular allosteric binding regions for a variety of non-ACh ligands ( Maeda et al, 2019 ; Tolaymat et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the five muscarinic receptor subtypes, the M3 subtype (M 3 R) is a conditional oncogene when expressed in cells capable of proliferation [ 6 ]. M 3 R is widely expressed in the intestine and overexpressed in colon cancer [ 7 , 8 ]. We previously showed that activation of M 3 R governs key hallmarks of colon cancer progression including cell proliferation, survival, migration, and invasion [ 7 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%